Unique mutation patterns in anaplastic thyroid cancer identified by comprehensive genomic profiling. Issue 6 (13th February 2019) - Khan, Saad A.; Ci, Bo; Xie, Yang; Gerber, David E.; Beg, Muhammad S.; Sherman, Steven I.; Cabanillas, Maria E.; Busaidy, Naifa L.; Burtness, Barbara A.; Heilmann, Andreas M.; Bailey, Mark; Ross, Jeffrey S.; et al.
Abstract: Introduction: Anaplastic thyroid cancer (ATC) is a highly aggressive thyroid cancer. Those ATC with genomic alterations (GAs) in TSC2, ALK, and BRAF may respond to targeted therapies. Methods: Comprehensive genomic profiling on 90 ATC specimens identified base substitutions, short insertions and deletions, amplifications, copy number alterations, and genomic rearrangements in up to 315 cancer‐related genes and 28 genes commonly rearranged in cancer. Results: Median patient age was 65 (range, 33‐86) years, 50 patients were male. There was a mean of 4.2 GA per case, range 1‐11. The most common GA were TP53 (66%), BRAF (34%), TERT (32%), CDKN2A (32%), and NRAS (26%). BRAF V600E and NRAS / HRAS/KRAS alteration were mutually exclusive. BRAF, CDKN2A, PIK3CA, and JAK2 were more frequent in patients >70 years of age; while myc, PTEN, and NRAS were more common in those ≤50 years. Conclusion: ATC shows many GA with potential therapeutic significance and suggesting different molecular pathways can lead to ATC.